A Comparison of Effectiveness of Dry Needling and Cross-Fiber Massage on Pain and Functional Mobility in Individuals with Chronic Lateral Epicondylitis - Munir, Mariha; Husnain, Ali; Mahmood, Husnain; Rauf , Amna; Shaheen, Aiman (Indus Journal of Bioscience Research, 2025)
Background: Lateral epicondylitis (LE), or tennis elbow, is a prevalent musculoskeletal condition characterized by lateral elbow pain and reduced function; primarily affecting adults aged 40–59. Although various conservative treatments exist, including dry needling (DN) and cross-fiber massage (CFM), limited evidence directly compares their effectiveness in chronic LE. Objective: To compare the effectiveness of DN and CFM on pain intensity, functional disability, and grip strength in individuals with chronic LE. Methods: A single-blind randomized clinical trial was conducted involving 60 participants aged 30–60 years diagnosed with chronic LE. Participants were randomly assigned to DN (n=30) or CFM (n=30) groups. Interventions were administered twice weekly for four weeks. Pain, disability, and grip strength were assessed using the Visual Analog Scale (VAS), Patient-Rated Tennis Elbow Evaluation (PRTEE), and a handheld dynamometer, respectively, at baseline and post-intervention. Results: Both groups showed significant within-group improvements in VAS, PRTEE, and grip strength scores (p<0.05). Between-group comparison revealed that the CFM group had significantly lower post-treatment VAS scores (p=0.007), while no statistically significant differences were observed between groups for PRTEE (p=0.55) or grip strength (p=0.819). Conclusion: Both DN and CFM are effective in managing chronic LE. However, CFM provided superior pain reduction, likely due to its mechanical effects on fibrotic tendon tissue. Clinicians should consider patient-specific factors when selecting between these interventions. Further studies with long-term follow-up and imaging-based evaluation are recommended.